Polyhydroxylated 2-styrylchromones and –xanthones as potent antioxidante agentes - Santos, Clementina M.M. (2012)
Chromones and xanthones are two classes of oxygenated heterocyclic compounds widely distributed in natureY1 Both natural and synthetic derivatives have been reported to exhibit biological, pharmacological and biocidal properties.11.21 The antioxidant capacity deserves a special mention and the structure-activity studies indicate that a substitution pattern that includes the presence of phenolic and/or catecholic moieties is highly important. 131 Inspired by the chemical structures of natural products we developed new routes for the synthesis of the quite rare family of 2-styrylchromones 1 and challenged us to design novel bioactive derivatives. 141 The reactivity of 3-bromo-2-styrylchromones was explored for the synthesis of unique examples of 2,3-diarylxanthones 2.151 Moreover, we focus our attention in the potential value of the hydroxylated 2-styrylchromones and -xanthones in order to establish structure-antioxidant activity relationships. 161 Highlights of our efforts towards the synthesis, spectroscopic characterization and antioxidant profile of chromones 1 and xanthones 2 and of all the intermediates will be presented and discussed.